The Diethylcarbamazine Delays and Decreases the NETosis of Polymorphonuclear Cells of Humans with DM Type 2 - Juan C. Segoviano-Ramirez; Daniel F. Lopez-Altamirano; Jaime Garcia-Juarez; Juan E. S. Aguirre-Garza; Eloy Cárdenas-Estrada; Jesús Ancer-Rodriguez (Journal of Diabetes Research)
Type 2 diabetes mellitus (DM2) is a disease that reports high morbidity and mortality rates worldwide. Between its complications, one of the most important is the development of plantar ulcers. The role of the polymorphonuclear cells (PMNs) is affected by metabolic diseases like DM2. Fifteen years ago, reports about a new mechanism of innate immune response where PMNs generate some kind of webs with their chromatin were published. This mechanism was called NETosis. Also, some researchers have demonstrated that NETosis is responsible for the delay of the ulcer healing both in patients with DM2 and in animal models of DM2. Purified PMNs from healthy and DM2 human volunteers were incubated with diethylcarbamazine (DEC) and then induced to NETosis using phorbol 12-myristate 13-acetate (PMA). In a randomized blind study model, the NETosis was documented by confocal microscopy. On microphotographs, the area of each extracellular neutrophil trap (NET) formed at different times after stimuli with PMA was bounded, and the intensity of fluorescence (IF) from the chromatin dyed with 4′,6-diamidino-2-phenylindole dihydrochloride (DAPI) was quantified. PMNs from healthy volunteers showed the development of NETs at expected times according to the literature. The same phenomenon was seen in cultures of PMNs from metabolically controlled DM2 volunteers. The use of DEC one hour before of the challenge with PMA delayed the NETosis in both groups. The semiquantitative morphometric analysis of the IF from DAPI, as a measure of PMN’s capacity to forming NETs, is consistent with these results. The ANOVA test demonstrated that NETosis was lower and appeared later than expected time, both in PMNs from healthy (p≤0.000001) and from DM2 (p≤0.000477) volunteers. In conclusion, the DEC delays and decreases the NETosis by PMNs from healthy as well as DM2 people.